Disboyizisin Önlenmesi ve Sağlıklı Mikrobiyota Gelişimi için Probiyotikler - Çakır, Adem; Arslan, Müge; Sadioğlu, Özgür Deniz; Akdemir, Tarık; Az, Adem; Güven, Şirin; Ümit, Tuba Betül; Şamlı, Mücahide; Çalık, Mustafa; Coşkun, Abuzer; Alkan, Mehmet Oktay; Altınbilek, Ertuğrul; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-